Delayed Presentation of Traumatic Intraperitoneal Rupture of Urinary Bladder. (5th December 2012) - Alhamzawi, Hazim H.; Abdelrahman, Husham M.; Abdelrahman, Khalid M.; El-Menyar, Ayman; Al-Thani, Hassan; Latifi, Rifat
Abstract : Blunt injury of the urinary bladder is well known and usually associates pelvic fractures. Isolated bladder injury is a rare condition and on the other hand, delayed bladder perforation is an extremely rare entity. Herein, we described an unusual case of isolated delayed intraperitoneal bladder rupture that occurred on the third post injury day in a young male in the absence of free intraperitoneal fluid and pelvic fracture. The diagnostic workup, course and the need for surgical repair of the injury is presented.